Operation of Water Resource Recovery Facilities, MOP11, 7e - Water Environment Federation (McGraw-Hill Education, 2017)
Delivers state-of-the-art guidance on best practices in the operation, management, and maintenance of water resource recovery facilities. Now conveniently presented in one volume, this authoritative reference reflects the role of 21st-century facilities in recovering valuable resources, including water, nutrients, and energy, and also features updated information on activated sludge, anaerobic digestion, biological nutrient removal, chemical handling, dissolved air flotation, fixed-film processes, maintenance, odor management, and safety and security.